Characterization of gastrointestinal absorption of digoxin involving influx and efflux transporter in rats: application of mdr1a knockout (−/−) rats into absorption study of multiple transporter substrate. (November 2014) - Suzuki, Motoya; Komura, Hiroshi; Yoshikawa, Tomonori; Enya, Seiji; Nagao, Akemi; Takubo, Hiroaki; Kogayu, Motohiro
Abstract 1. <?ri?>This study was aimed to characterize gastrointestinal absorption of digoxin using wild-type (WT) and multidrug resistance protein 1a [mdr1a; P-glycoprotein (P-gp)] knockout (−/−) rats. 2. <?ri?>In WT rats, the area under the plasma concentration–time curve (AUC) of oral digoxin increased after oral pretreatment with quinidine at 30 mg/kg compared with non-treatment, but the increasing ratio tended to decrease at a high dose of 100 mg/kg. In mdr1a (−/−) rats, however, quinidine pretreatment caused a dose-dependent decrease in the AUC. 3. <?ri?>Quinidine pretreatment did not alter the hepatic availability of digoxin, indicating that the changes in the digoxin AUC were attributable to inhibition of the absorption process by quinidine; i.e. inhibition of influx by quinidine in mdr1a (−/−) rats and inhibition of efflux and influx by quinidine in WT rats. 4. <?ri?>An in situ rat intestinal closed loop study using naringin implied that organic anion transporting peptide (Oatp) 1a5 may be a responsible transporter in the absorption of digoxin. 5. <?ri?>These findings imply that the rat absorption behavior of digoxin is possibly governed by Oatp1a5-mediated influx and P-gp-mediated efflux. The mdr1a (−/−) rat is therefore a useful in vivo tool to investigate drug absorption associated with multiple transporters including P-gp.